Increased activation of the hypoxia-inducible factor pathway in varicose veins. - Lim, C; Kiriakidis, S; Paleolog, E; Davies, A (2012)
BACKGROUND: Venous hypoxia has been postulated to contribute to varicose vein (VV) formation. Direct measurements of vein wall oxygen tension have previously demonstrated that the average minimum oxygen tensions were significantly lower in VVs compared with non-varicose veins (NVVs). Hypoxia-inducible factors (HIFs) are nuclear transcriptional factors that regulate the expression of several genes of oxygen homeostasis. This study aimed to investigate if hypoxia was associated with VVs by assessing the expression of HIF-1α, HIF-2α, HIF target genes, and upstream HIF regulatory enzymes in VVs and NVVs, and their regulation by hypoxia. METHODS: VVs and NVVs were surgically retrieved and immediately snap-frozen or used for organ culture preparation. The relative expression of HIF-1α, HIF-2α, HIF target genes, and HIF regulatory enzymes in VVs and NVVs was analyzed with quantitative polymerase chain reaction (Q-PCR) and Western blot. VV and NVV organ ex vivo cultures were exposed to 16 hours of normoxia, hypoxia (oxygen tension 1%), or the hypoxia mimetic dimethyloxallyl glycine (DMOG) 1 mM in normoxia. The vein organ cultures were then analyzed for HIF-1α, HIF-2α, and their target gene expression with Q-PCR and Western blot. RESULTS: HIF-1α and HIF-2α mRNA were significantly upregulated in VVs compared with NVVs (89.8 ± 18.6 vs 10.4 ± 7.2 and 384.9 ± 209.4 vs 8.1 ± 4.2, respectively). HIF target gene mRNA expression was also significantly elevated in VVs compared with NVVs, namely glucose transporter-1 (GLUT-1; 8.7 ± 2.1 vs 1.0 ± 0.3), carbonic anhydrase-9 (CA9; 8.5 ± 2.1 vs 2.8 ± 1.2), vascular endothelial growth factor (VEGF; 7.5 ± 2.1 vs 0.9 ± 0.2), and BCL2/adenovirus E1B 19-kDa protein-interacting protein 3 (BNIP-3; 4.5 ± 0.7 vs 1.4 ± 0.3). The upregulation of HIF-1α, HIF-2α, and HIF target genes in VVs was also reflected at protein level. Of the HIF regulatory enzymes, the expression of prolyl-hydroxylase domain (PHD)-2 and PHD-3 was found to be elevated in VVs compared with NVVs. Exposure of VV and NVV organ cultures to hypoxia or DMOG was associated with increases in HIF-1α and HIF-2α protein and HIF target gene expression compared with normoxia only. CONCLUSIONS: The study concluded, we believe for the first time, an increased activation of the HIF pathway, with upregulation of the expression of HIF-1α and HIF-2α transcription factors, and HIF target genes, in VVs compared with NVVs. Exposure of VVs and NVVs to hypoxic conditions was associated with increased expression of HIF-1α and HIF-2α protein and HIF target genes. The data suggest that the HIF pathway may be associated with several pathophysiologic changes in the VV wall, and that hypoxia may be a feature contributing to VV pathogenesis.